2016
DOI: 10.1007/s00125-016-3863-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics uncovers the role of adipose tissue PDXK in adipogenesis and systemic insulin sensitivity

Abstract: Aims/hypothesis We aimed to investigate the potential mechanisms involved in the compromised adipogenesis of visceral (VAT) vs subcutaneous adipose tissue (SAT) using comparative metabolomics. Based on the differentially identified metabolites, we focused on the relationship between the active form of vitamin B 6 (pyridoxal 5-phosphate [PLP]), known to be generated through pyridoxal kinase (PDXK), and adipogenesis. Methods Non-targeted metabolomics analyses were performed in paired VAT and SAT (n = 14, discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 46 publications
3
23
0
1
Order By: Relevance
“…In addition, PEO treatment increases the biosystem of Pyridoxal (VB6) and Pantothenate in the cecal contents. Pyridoxal participates protein and sugar metabolism 57 , and the active form of VB6 is linked with adipogenesis 58 . These results indicate that PEO might alter different lipid metabolites and vitamins from AGP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PEO treatment increases the biosystem of Pyridoxal (VB6) and Pantothenate in the cecal contents. Pyridoxal participates protein and sugar metabolism 57 , and the active form of VB6 is linked with adipogenesis 58 . These results indicate that PEO might alter different lipid metabolites and vitamins from AGP.…”
Section: Discussionmentioning
confidence: 99%
“…The higher activity of methanogenesis is in line with the higher relative abundances of methanogenic archaea in the FL samples. A recent study found that the active form of vitamin B6 (pyridoxal 5-phosphate) is linked with adipogenesis using a comparative metabolomic approach76.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic disorder of PDXK activity can result in metabolic disorder of amino acids, which may be the pathogenesis of the secondary injury of nervous system and other neurological damage. 20, 21 PDXK is distributed in the cytoplasm of spinal cord neurons and glial cells, which maintain the dynamic equilibrium of the pyridoxal phosphate concentration to restore stability of the SCI microenvironment, and PDXK is also the target protein for miR-124 to inhibit. 22 Therefore, it was found that miR-124 was a negative regulator of PDXK, and it conferred an inhibitory effect on PDXK expression.…”
Section: Discussionmentioning
confidence: 99%